Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1177/1464420720910442
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the process parameters and mechanical properties of laser butt welds in thin high strength low alloy steel plates

Abstract: High strength low alloy steels subjected to the thermomechanical control process present excellent strength–toughness combination, high strength/weight ratio, and weldability. Therefore, they are widely used in structural components, such as pressure vessels, oil/gas transportation pipes, lifting equipment, vehicles, shipbuilding and offshore industries, and in the automotive industry where low thickness (0.8–3 mm thickness) is of great importance. Usually, these steels are welded by conventional gas metal arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Figure 2 presents a representative example of metallographic analysis where Figure 2b corresponds to underfill defect, Figure 2c shows the toe of the weld root and Figure 2d illustrates an undercut defect. For the heat input range used in the present work, Figure 2b showed that the HAZ was divided into two important zones: softened ferritic-bainitic with fine grain (FG) and bainitic-martensitic with coarse grain (CG) as was found in [29]. Figure 2b also shows the macrostructure of the FZ and the BM.…”
Section: Welding Defects and Hardnessmentioning
confidence: 63%
See 2 more Smart Citations
“…Figure 2 presents a representative example of metallographic analysis where Figure 2b corresponds to underfill defect, Figure 2c shows the toe of the weld root and Figure 2d illustrates an undercut defect. For the heat input range used in the present work, Figure 2b showed that the HAZ was divided into two important zones: softened ferritic-bainitic with fine grain (FG) and bainitic-martensitic with coarse grain (CG) as was found in [29]. Figure 2b also shows the macrostructure of the FZ and the BM.…”
Section: Welding Defects and Hardnessmentioning
confidence: 63%
“…This steel is composed of a fine-grain ferritic-bainitic microstructure. The chemical composition can be consulted in Table 1 and this material showed a yield strength of 808 MPa, a tensile strength of 838 MPa and 15% of elongation at failure [29]. Five series were welded using the parameters presented in Table 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the heat sources is laser, which is now widely used for welding and material processing [11][12][13][14] and can potentially be used to weld a container. Steels with BCC [15][16][17] and FCC [18][19][20] crystallographic space groups, aluminum alloys [21], titanium alloys [22], nickel alloys [23], plastics [24], and composites [25] can be laser beam welded. These joints are characterized by a narrow weld and a heat-affected zone with mechanical properties similar to those of joints made with conventional electric arc processes [26] and often exceeding them.…”
Section: Requirements For the Ferrofluid Containermentioning
confidence: 99%
“…In recent years, there are many researchers investigating the high-strength dissimilar metal laser welded joints with a different thicknesses. Gustavo [30] has studied the relationship between the process parameters and the geometry size of laser welded joint of high strength low alloy steel (HSLA). They found that as the laser power increases or welding speed decreases, the width and the penetration of the welded joints increases, which is consistent with our experiment results (show in figures 5-7).…”
Section: Effect Of Welding Speed On the Mechanical Properties Of Weldmentioning
confidence: 99%